Android-Based Learning Media Development to Improve Student Learning Achievement - Mujiono Mujiono; Siti Sarah (Berkala Ilmiah Pendidikan Fisika, 2021)
Android media is one of the learning media that is easy and interesting to use. This study aimed to develop an Android-based science learning media that fulfills valid, practical, and effective aspects. The research method used 3 stages of the 4D model, namely (1) define, (2) design, and (3) develop. The dissemination stage was not done because it took a long time. The research instruments were validation sheets, questionnaire, and test. The media validity test was carried out by material experts and media experts. Practicality tests were carried out by teachers and students. The effective tests were carried out by student. The data analysis techniques were qualitative and quantitative descriptive analysis. The effective test used a quasi-experimental method with an intact-group comparison design. The results showed that the android-based science learning media fulfilled valid criteria by material experts and media experts. The android-based science learning media fulfilled practical criteria by junior high school science teachers and students. There were differences in learning achievement for students who used Android-based science media and those who learned without using the media. The learning achievement for students who used Android-based science learning media was better than the students who learned without using android-based science learning media; this media can be the alternative of online learning.